Revisitando a História da Matemática e enfatizando aspectos de sua formação (composição, consolidação) no campo da Educação Matemática: Revisiting the History of Mathematics and emphasing aspects of its formation (composition, consolidation) in the field of Mathematics Education (Revista Cocar, 2022)
Neste artigo objetivamos apresentar aspectos da formação (composição, consolidação) da História da Matemática no campo da Educação Matemática. Desta forma, em uma revisita, enfatizamos aspectos que nos apresentam a história da matemática como uma disciplina instituída em cursos de graduação de matemática, suas origens como tendência metodológica e de pesquisa com destaque para sua objetivação e o seu uso em salas de aula de matemática. Para isso, trazemos referência a pesquisadores que vem desenvolvendo pesquisas nesta área, apresentando alguns de seus trabalhos que coadunam de forma efetiva com a pesquisa que vimos realizando e que enfatiza o uso da história da matemática como componente metodológica a partir das atividades obtidas do estudo de “textos históricos” considerando suas potencialidades didáticas para o ensino de conteúdos matemáticos.Palavras-chave:  História da Matemática; Ensino de Matemática; Textos Históricos AbstractIn this paper, we aim to present aspects of the formation (composition, consolidation) of the History of Mathematics in the field of Mathematics Education. Thus, in a revisit, we emphasize aspects that introduce us to the history of mathematics as a discipline instituted in undergraduate mathematics courses, its origins as a methodological and research trend with emphasis on its objectification and its use in mathematics classrooms. For this, we bring reference to researchers who have been carrying out research in this area, presenting some of their works that are effectively in line with the research we have been carrying out and which emphasizes the use of the history of mathematics as a methodological component based on the activities obtained from the study of “historical texts” considering their didactic potentialities for teaching mathematical contents.Key words: History of Mathematics; Teaching of Mathematics; Historical Texts